Indonesia - simbolon, amril; Natalia, Erni Yanti (LPPM Universitas Putera Batam, 2021)
ABSTRACT This Analysist created in hope to explain how huge the s influence of investment decisions and policies dividends, on how much the companies valued in the manufacturing company in goods industry sub-sector that appeared on IDX in the period of 2015–2019. how this data fomulated is using multiple linear regression, non probabillity and et cetera.whilu using sample of 14 companies from 193 companies, after being reduced to succh amount, which also have set up their reports financials statements consistly through out 2015-2019 periods that been audited and companies absolutely owning a complete data on investment decisions and dividend policy in 2015- 2019 in manufacturing companies that appears on the IDX. mainly the secondary data is used as quantitative in the form of numbers. The data is formulated with the help of SPSS program version 22. result of this study show it partial investment decisions in manufacturing companies have a significant effect on the value of firm and dividend policy have a significant effect on firm value. By Simultaneous decisions and dividen policy is affecting simultaneously to how valueable the company is.